THE ANALYSIS OF EXTRAVERT TYPES IN THE BOOKISH LIFE OF NINA HILL: A Novel By Abbi Waxman - Ismawati, Iis; Adrallisman, Adrallisman (e-LinguaTera, 2022)
Abstract This thesis analyzes Extravert personality types in the novel ‘The Bookish Life Of Nina Hill’. The goals of this research is to find out what type of extravert personality that can be seen in the novel ‘The Bookish Life Of Nina Hill’ which is related to the personality approach using Carl Jung's personality theory. This research focuses on Nina Hill's personality. The reason is because Nina Hill's personality is a nerd girl who wants to change her life to become more open to the world. The method that is used for this thesis is a qualitative method by collecting data through library books and online data. The results show that extravert personality types found in the novel are divided into four types namely Thinking, Feeling, Sensing, and Intuiting. The first is Extravert Thinking. It is a personality that She thinks logically so that She is understanding and explaining things with logical rules. Second is Extravert Feeling. It is a personality that shows She responds to something emotionally. She is rejecting opinions that do not suit her emotionally. Third is Extravert Sensing. It is a personality who seeks pleasure by enjoying her activities in her weekly activities. Furthermore, Extravert Intuiting. It is a personality that She has creativity and takes advantage of the opportunity by making new ideas and taking advantage of opportunities to increase her knowledge.